ANALISIS KURIKULUM 2013 DI TK NURUL IMAN KECAMATAN KEMUNING PALEMBANG - Lidia Oktamarina; Sukma Ayu; Ana Zakiati Fakhiroh; Resky Dwi Yanti; Septaria (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This research was conducted at Nurul Iman Kindergaten, Kemuning District, Palembang. This research aims to describe the implementation precess of the 2013 PAUD Curriculum at Nurul Iman Kindergaten. This research uses a qualitative approach and descriptive research type. The research subject were 13 teachers at Nurul Iman Kindergaten, while the object if this research was the 2013 PAUD curriculum. Data collection techniques use interview, observation and document study. The data analysis technique used is descriptive qualitative with the miles and Huberman interactive analysis model, namely data collection, data reduction, data presentation and drawing conclusions. The validity of the research data was tested using technical triangulation. The research results show that Nurul Iman Kindergaten implements the 2013 PAUD Currikulum which includes the process of preparation process of preparation, implementation and evaluation of learning. The learning preparation process includes preparing the prosem, formulating the theme, preparing the RPPM and preparing the RPPH. The implementation process includes all learning process from start to finish. The evaluation process includes various evaluation technique applied by teachers. Keyword: implementation study, curriculum, 2013 early childhood education curriculum.